Continuous Synthesis of Multi-Walled Carbon Nanotubes from Xylene Using the Swirled Floating Catalyst Chemical Vapour Deposition Technique - Unuabonah, Emmanuel (Springer, 2011)
This work reports the continuous and large-scale production of multiwalled carbon nanotubes (MWCNTs) from xylene/ferrocene in a swirled floating catalyst chemical vapor deposition reactor using argon as the carrier gas. The concentration of ferrocene used was 0.01 g/mL of xylene. In every run, 50-mL xylene gas was used together with xylene/ferrocene mixture injected into the reactor by means of a burette. The MWCNTs produced were characterized using the transmission electron microscopy (TEM) and Raman spectra. TEM analysis showed a poor production rate at 850 °C and a good production in the range of 900–1000 °C with optimal production rate at 950 °C. Furthermore, xylene/ferrocene mixture produced more MWCNTs at 950 °C with H:Ar (1:7) as the carrier gas. The diameters of the MWCNTs in the temperatures studied ranged from 15 to 95 nm with wall thicknesses between 0.5 and 0.8 nm.